Sistem Informasi Sewa Rumah Kost Dan Rumah Kontrakan Berbasis Web Di Surakarta - Didit Gunawan; Ernes Cahyo Nugroho (STIE AUB Surakarta, 2015)
The use of information systems in business is needed for the development, exchange of information electronically to the application of business strategies, such as: marketing, sales, and customer service . So also in the field of commodity properties for rent boarding houses and rented houses. The development of information systems increasingly fast can put to good use through a lot of things in the system, but some managers and prospective tenants boarding home rental business and rented houses are still experiencing difficulties in having an integrated system. Many of them are still making sales / reservation directly in everyday life. In terms of the consumer, still have to make purchases at the location where the manager was and limited information about the available types. Boarding houses and rented houses a rental dwelling that is destined for temporary shelter, in the case study authors wanted to use information systems to allow people to find a boarding house and Houses Rented Houses in accordance with the information needs or the needs of one's home. With the creation of the system in Information Systems Rent House Rented in Surakarta boarding and web-based, it can be several conclusions, among others, have created a web-based system that can be accessed through the website by logging in at capacity level as well as the users of this system can assist in the billing process, assist in providing information to consumers about the waiting time and the status of reservations effectively.Keywords : Systems , Information , Website , Dorm , House , Rented , Effective